Non-Intubated Thoracic Surgery: Standpoints and Perspectives - Anile, Marco; Vannucci, Jacopo; Ferrante, Francesco; Bruno, Katia; De Paolo, Dalila; Bassi, Massimiliano; Pugliese, Francesco; Venuta, Federico; , the NIVATS Interest Group; Diso, Daniele; Poggi, Camilla; Pecoraro, Ylenia; et al. (Frontiers in Surgery, 2022)
Non-intubated video-assisted thoracic surgery (NI-VATS) combines the advantages of a non-intubated surgery with the benefits of a minimally invasive approach. First, NI-VATS is performed in the case of fragile patients when general anesthesia and/or orotracheal intubation can be foreseen as inconvenient. However, NI-VATS indications have been increasingly extended to different patient conditions, considering the increasingly assessed safety and feasibility of the procedure. Currently, the NI-VATS approach is used worldwide for different thoracic surgery procedures, including the management of malignant pleural effusion, surgical treatment of empyema, anatomical and non-anatomical lung resection, and other indications. In fact, this approach has shown to be less impactful than VATS under general anesthesia, allowing for shortened hospitalization and faster recovery after surgery. Besides, NI-VATS is associated with fewer pulmonary complications, less respiratory distress, and a mild systemic inflammatory reaction. For these reasons, this approach should be considered not only in patients with poor cardiac or respiratory function (general functional reserve), but also in other eligible conditions. We explored the anesthetic and surgical aspects of such an approach, including the management of analgesia, cough reflex, depth of sedation, and intraoperative technical issues to put this approach in perspective.